THE POTENTIAL ROLE OF THE MILITARY IN NATIONAL DEVELOPMENT - Heitman, H.R. (Scientia Militaria - South African Journal of Military Studies, 2012)
Apart from certain political and economic problems, there is one thing that all less developed countries have in common: some form or other of a military establishment. These vary widely in size and sophistication, ranging from Benin’s 1 650 men, 5 armoured cars, 6 transports and one helicopter, to India’s 1 055 500 men, approximately 1 900 tanks, 4Q-odd major combat vessels including 1 aircraft carrier and some 980 combat and 200 transports and around 300 helicopters. While the military establishments of the less developed countries vary as widely as most other aspects of their countries they too have something in common: all have some capability for political intervention and/or assisting development in the economic and technical field. This paper shall attempt to present a short oveNiew of some of the military establishment’s non-martial capabilities and their utilizations.